2010
DOI: 10.3949/ccjm.77.s3.04
|View full text |Cite
|
Sign up to set email alerts
|

Depression and cardiovascular disease: Selected findings, controversies, and clinical implications from 2009

Abstract: We systematically searched published empirical research on depression and cardiovascular disease (CVD) and found 494 unique articles published in 2009. Herein, we present selected provocative findings or interesting controversies, and, where appropriate, we discuss the clinical implications of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
0
17
1
Order By: Relevance
“…Even if almost half of the 57 studies reviewed by Wulsin et al (1999) [27] failed to show any association between depressive symptoms and mortality, several published studies showed that major depression is associated with poorer outcome of medical disorders. Our results are at odds with this literature, which however is controversial, since it failed to show that treating major depression can improve outcome of medical disorders, especially cardio-vascular diseases [28]. Three major points may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 77%
“…Even if almost half of the 57 studies reviewed by Wulsin et al (1999) [27] failed to show any association between depressive symptoms and mortality, several published studies showed that major depression is associated with poorer outcome of medical disorders. Our results are at odds with this literature, which however is controversial, since it failed to show that treating major depression can improve outcome of medical disorders, especially cardio-vascular diseases [28]. Three major points may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 77%
“…If our results are confirmed, they may have practical implications. Systematic screening for depressive symptoms should be recommended in liver transplant recipients, even if recent literature in cardiac patients [31] suggests that such screening may be of dubious value. Whether interventions based on depressive symptoms after LT could decrease long-term mortality should now be assessed in further studies.…”
Section: Discussionmentioning
confidence: 97%
“…4,5 In 2008, concern about these deleterious effects led the American Heart Association, with an endorsement from the American psychiatric Association, to publish a scientific advisory 1 calling for routine screening of depression in CHD patients.…”
Section: Methodsmentioning
confidence: 99%